2001
DOI: 10.1046/j.1365-3032.2001.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physiological status on olfactory and visual responses of female Hypothenemus hampei during host plant colonization

Abstract: Summary The response of Hypothenemus hampei (Ferr.) (Coleoptera, Scolytidae) (coffee berry borer, CBB) females to olfactory stimuli was demonstrated to be related with the physiological status; especially with age, whether they were mated or not, and whether they have already oviposited. A special behaviour, the abandonment of the native berry, was also found to play a major role. In contrast, response to visual stimuli (false coffee berries) was found to be independent of the physiological status of CBB femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 8 publications
0
38
1
26
Order By: Relevance
“…These last ones have been proposed elsewhere (Villacorta et al, 2001 andBarrera et al, 2004) and farmers use both due to their availability, without information about their relative efficiency. Red traps were also used because previous studies reported an attraction of coffee berry borers to the red color which mimic the color of ripe berries (Mendonza Mora, 1991;Giordanengo et al, 1993) and were prepared by coating transparent bottles with red paint (Coral Dulux ® , 350 red). Traps were baited with an Ethanol : Methanol mixture (1:1).…”
Section: Trap Colorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These last ones have been proposed elsewhere (Villacorta et al, 2001 andBarrera et al, 2004) and farmers use both due to their availability, without information about their relative efficiency. Red traps were also used because previous studies reported an attraction of coffee berry borers to the red color which mimic the color of ripe berries (Mendonza Mora, 1991;Giordanengo et al, 1993) and were prepared by coating transparent bottles with red paint (Coral Dulux ® , 350 red). Traps were baited with an Ethanol : Methanol mixture (1:1).…”
Section: Trap Colorsmentioning
confidence: 99%
“…Scolytids are attracted to ethanol (E) (Moeck et al, 1981) and methanol (M) (Moeck, 1970) and this is also true for CBB in the field (Mendonza Mora, 1991;Mathieu et al, 1999). It is probable that the conditions under which coffee is grown (climate, spacing, shade, cultivar, plant age, wind direction, speed etc) may affect trapping efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesta fase, são atraídas por compostos voláteis dos frutos, etanol (E) e metanol (M), porém quando ainda não saíram dos frutos, estas fêmeas não apresentam respostas a estes semioquímicos (MATHIEU et al, 1991). Já em relação às respostas a estímulos visuais, todas as fêmeas mostram-se responsivas.…”
Section: Estímulos Visuaisunclassified
“…Tal preferência foi demonstrada em estudos em laboratório e no campo (MENDONZA-MORA, 1991;GIORDANENGO;FRÉROT, 1993;MATHIEU et al, 1997b;MATHIEU et al, 1991). Todavia, os resultados de estudos envolvendo a seleção de cores por fêmeas da broca-do-café são conflitantes, reforçando a hipótese de que vários fatores, além da cor, estão envolvidos no processo de localização e colonização de frutos de café por fêmeas de H. hampei (MENDONZA-MORA, 1991;FRÉROT, 1997a).…”
Section: Estímulos Visuaisunclassified